Indian art - Mitter, Partha (Oxford : Oxford University Press, 2001)
This concise yet lively new survey guides the reader through 5,000 years of Indian art and architecture. A rich artistic tradition is fully explored through the Hindu, Buddhist, Islamic, Colonial, and contemporary periods, incorporating discussion of modern Bangladesh and Pakistan, tribal artists, and the decorative arts. Combining a clear overview with fascinating detail, Mitter succeeds in bringing to life the true diversity of Indian culture. The influence of Islam on the Mughal court, which produced the world-famous Taj Mahal and exquisite miniature paintings, is closely examined. More recently, he discusses the nationalist and global concerns of contemporary art, including the rise of female artists, the stunning architecture of Charles Correa, and the vibrant art scene. The very particular character of Indian art is set within its cultural and religious milieu, raising important issues about the profound differences between Western and Indian ideas of beauty and eroticism in art. --Publisher.
1. Introduction -- 2. Buddhist Art and Architecture -- 3. Hindu Art and Architecture -- 4. Minority Traditions, Ideal Beauty, and Eroticism -- 5. The Turko-Afghan Sultanate of Delhi (1206-1526 CE)-- 6. The Mughal Empire (1526-1757) -- 7. Rajasthani and Pahari Kingdoms (c.1700-1900) -- 8. The Non-Canonical Arts of Tribal Peoples, Women, and Artisans -- 9. The British Raj: Westernization and Nationalism -- 10. Modernism in India -- 11. Art After Independence -- 12. The Contemporary Scene.
Includes bibliographical references, index and list of museums and websites.
Keywords: Art, Indic; Architecture -- India; Art, Indic -- History; Art, Hindu -- History; Architecture -- India -- History